Enhancing insulin secretion by pancreatic β-cell redifferentiation: a study of the anti-diabetic effects of berberine in vitro - Xing, Jing-Jing; Li, Wei; Chen, Chen (Frontiers in Endocrinology, 2025)
The β-cell dedifferentiation and impaired glucose-stimulated insulin secretion (GSIS) contribute to the pathogenesis of diabetes. Berberine (BBR), a natural compound with known anti-diabetic therapeutic properties, has been investigated for its potential role in preserving β-cell function. This study aims to elucidate the molecular mechanism by which BBR prevents β-cell dedifferentiation and restores deteriorated GSIS. In this in vitro study, the MIN-6 and INS-1 pancreatic β-cell lines were exposed to a FoxO1 inhibitor, excessive levels of H2O2 or free fatty acids (FFAs) to induce dedifferentiation and impaired GSIS. BBR treatment was administered to assess its impact on β-cell fate and function. Molecular analyses, including gene expression profiling and pathway analysis, were conducted to unravel the underlying molecular mechanisms. BBR treatment significantly reduced β-cell dedifferentiation induced by FoxO1 inhibitor, H2O2 and FFAs. BBR treatment effectively reversed the poor GSIS observed under the FoxO1 inhibition and high concentrations of H2O2 and FFAs, restored the ability of β cells to respond normally to glucose by secreting insulin. The protective effect was associated with the modulation of nuclear factor kappa B (NF-κB) signaling pathway, while BBR reduced the overproduction of NF-κB, which has been proved by applying NF-κB angoist in INS-1 cell line. This study explored the protective potential of BBR in preventing β-cell dedifferentiation and restoring impaired GSIS, under the conditions of FoxO1 inhibition, excessive levels of H2O2 and FFAs. BBR may therefore be a promising candidate for diabetes treatment. In-vivo experiments are warranted to evaluate dedifferentiation levels in rodent diabetic models and the efficacy of BBR on the pancreatic β-cell redifferentiation in diabetes.